The Relationship Betweem Self Image and Prosocial Behavior in Instagram Social Media Users - Rafidatunnisa; Kurniati Zainuddin; Tri Sulastri (PT ARRUS Intelektual Indonesia, 2024)
Instagram is one of the biggest platforms used by all groups of people. Instagram provides various kinds of knowledge information and social assistance such as helping behavior or what is known as prosocial behavior. Prosocial behavior is the behavior of helping each other among individuals. Instagram is also used as a place for the formation of selfimage. Selfimage is a view and image of oneself, self-image is formed from past experiences and individual behavior. The research method used is quantitative method. The subjects in this study were Instagram users, age 18-29 years who were obtained using the sperman rho technique with the accidental sampling method. The research data was tested using the Cronbach's alpha reliability test using the SPSS application. The measuring tools used in this research are self-image scale and prosocial behavior scale. The results showed that there was a positive relationship between self-image and prosocial behavior on Instagram social media users, which was 0.232 (p<0.001), meaning that there was a positive relationship between the two variables. The purpose of study was to determine the relationship between self-image and prosocial behavior on Instagram social media users.